Synthesis and thermodynamic properties of amorphous calcium phosphate - Kohutová, Anna; Pilný, Petr; Honcová, Pavla; Svoboda, Ladislav (University of Pardubice, 2011)
The formation of amorphous calcium phosphate (ACP) was studied in the context of urinary stones formation. Processes of ACP precipitation were observed in simulated medium: in aqueous solutions of potassium chloride and artificial urine (SRAU) at the ionic strength of 0.3 mol dm–3. Amorphous structure of calcium phosphate was verified by X-ray diffraction analysis and Raman spectroscopy. Thermochemical study of ACP precipitation was investigated by using the isoperibolic reaction twin calorimeter. The experiments were carried out at the initial concentrations of ACP in the range from 6 to 14 mmol dm–3 for KCl solution and 6-16 mmol dm–3 for SRAU. The ACP precipitation was performed by reaction of Ca2+ and ions with Ca:P molar ratio close to 1.5 at the temperatures of 298.15 K and 310.15 K. The molar enthalpy of ACP formation was calculated by use of ACP solubility which was determined in this work. Molar enthalpies of ACP formation, )Hm, are 29.8 ± 0.9 kJ mol–1 at 298.15 K and 36.3 ± 0.9 kJ mol–1 at 310.15 K in KCl solution, and )Hm 298.15 = 35.4 ± 1.3 kJ mol-1 and )Hm 310.15 = 41.6 ± 1.5 kJ mol–1 in SRAU.